PENERAPAN MODEL PEMBELAJARAN COOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELASV SD NEGERI 016 PANDAN AIR KECAMATANPERANAP KABUPATEN INDRAGIRI HULU - Haspita, R.Leni; Marhadi, Hendri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This research at performs since its low usufruct IPS'S studying student brazes V SDN 016 Pandan Air that haven't reached KKM (Minimum thoroughness criterion) one that is established which is 65. This appears from peneletian's startup data of 18 students which reach points according to KKM as much 8 students (44,44%), meanwhile student that haven't reached KKM'S point as much 10 students (55,56%). Base about problem research do that action brazes with learnings model implement kooperatif type Make a. Match one that intent to increase IPS'S studying result student brazes V SDN 016 Pandan Air School Year 2014 / 2015. This research is executed deep two cycles, whereabouts on each cycle it consisting of two-time appointment gazes to show face and once daily dry run. With be applied Model Kooperatif's Learning Type Make a. Match , therefore gets to increase IPS'S studying result student brazes V SDN 016 Pandan Air on preparation material until proclamation seconds. It can at see of studying result gotten by student on base score which is with thoroughness percentage 44,44%, with average 61,66, worked up on i. cycle with thoroughness percentage 66,67% by average 65,55. Worked up again on cycle II.which is with thoroughness percentage 94,44% by average 75. On Activity learns first cycle with percentage average 77,5% worked up as 92,1% on second cycle. Student activity on first cycle with percentage average 73,21% worked up as 89,25% on second cycle. Of acquired data as above as gets to be known that learnings model Implement kooperatif type Make a. Match , can increase IPS'S studying result student brazes V SDN 016 Pandan AirKey word: Make a. Match , IPS'S Learned result